Amazon: its space and its inhabitants - Schuindt , Elisangela; Sousa, Greissi Cristina (Seven Editora, 2023)
This scientific article seeks to discuss the fallacy of the superiority of the colonizer and the inferiority of the colonized in the context of the promised land of the Amazon. Dialoguing with the theoretical field of Cultural Studies, we weave a treadmill of memorialists and/or historical nature to diagnose, through bibliographical research, the possible changes in the vision of the colonizer, from his arrival in Brazil to this historical moment, about the colonized, that is, the natives. In the attempt to obtain a position in the face of the colonialist discourse, as a reductionist vision of the Amazon region and a mistaken view about the subject and the Amazonian space, we wish to guarantee representativeness to the multiple voices of the "identities" of the subjects who inhabit the Amazon. We think of the Amazon as the between-place, a means of excellence for dialogue between the present and the past, between the native and the foreigner, between the colonizer and the colonized. A unique place that transcends the boundaries of space and time. DOI: https://doi.org/10.56238/alookdevelopv1-036